2014
DOI: 10.1016/j.indcrop.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterization and antioxidant activity of three medicinal Apiaceae species

Abstract: a b s t r a c tCentella asiatica ('Pegaga' = Malaysia) is well known plant that has been used as one of the ingredients in pharmaceutical and cosmetic industries. Using liquid chromatography with diode array and electrospray ionization/mass spectrometry (LC-DAD-ESI/MS) analysis, chemical profiling of three different Pegaga extracts (C. asiatica, H. bonariensis and H. sibthorpioides) revealed variations in their metabolite profile. Our findings showed that triterpenes of C. asiatica were characterized by the ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 26 publications
4
26
0
Order By: Relevance
“…The presented results were in accordance with those previously described by Meot-Duros and Magné (2009) who reported that sea fennel was one of the most chlorogenic acid-rich Apiaceae plants. Similar observations could be made regarding the results on phenolics and chlorogenic acid content in other Apiaceae species (Pandey et al 2012;Maulidiani et al 2014).…”
Section: Chemical Compositionsupporting
confidence: 87%
“…The presented results were in accordance with those previously described by Meot-Duros and Magné (2009) who reported that sea fennel was one of the most chlorogenic acid-rich Apiaceae plants. Similar observations could be made regarding the results on phenolics and chlorogenic acid content in other Apiaceae species (Pandey et al 2012;Maulidiani et al 2014).…”
Section: Chemical Compositionsupporting
confidence: 87%
“…According to Güzel et al 8 the popularity of Lamiaceae and Asteraceae may be due to their aromatic characteristics and to their wide geographical spread. Several studies have confirmed the benefits of these families, according to Miliauskas et al 43 Khled Khoudja et al 44 Maulidiani et al 45 their importance lies in their high phenolic and flavonoid contents, compounds responsible for the antioxidant activity. Finally, in addition to their therapeutic role, the herbaceous families provide a favorable environment for the germination of the shrub layer seeds and the growth of young seedlings.…”
Section: Most Represented Botanical Familymentioning
confidence: 94%
“…The determination of the total phenolic content of the extracts was performed using Folin-Ciocalteu reagent as described by Maulidiani et al (2014). A 10 l alliquot of all the extracts (500 mg/ml) in triplicate was placed in a 96-well microplate followed by the addition of 25 l of freshly prepared Folin-Ciocalteu reagent (10-fold dilution).…”
Section: Total Phenolic Content Assaymentioning
confidence: 99%
“…The radical scavenging activity was determined according to Maulidiani et al (2014) with slight modification. Briefly, 150 l of DPPH (0.3 mM in ethanol) was added to 50 l of test extract in a 96-well microtiter plate.…”
Section: Dpph Free Radicals Scavenging Assaymentioning
confidence: 99%